Theoretical Study and Experimental Validation of Energetic Performances of Photovoltaic/Thermal Air Collector - Khaled Touafek; Abdelkrim Khelifa; Lyes Boutina; Ismail Tabet; Salim Haddad (International Journal of Photoenergy)
This work undertakes both simulation and experimental studies of a new design of a photovoltaic thermal solar air collector (PV/T). In order to improve the thermal and electrical performances for a specific application, the analytical expressions for thermal parameters and efficiency are derived by developing an energy balance equation for each component of the PV/T air collector. This type of hybrid collector can be applied in the facades of buildings. The electricity and heat produced will satisfy the energy needs of the buildings, while ensuring an aesthetic view of its facades. A typical prototype was designed, constructed, and implemented in the applied research unit on renewable energies in Ghardaia, situated in the south of Algeria. This region has semiarid characteristics. Results obtained by an experimental test are presented and compared to those predicted through simulation. Results include the temperature of each component of the PV/T collector and air temperature at the inlet and outlet of the channel. It has been found that the theoretical results predicted by the developed mathematical model, for instance, outlet temperature, agree with those found through experimental work.